Microsoft Exchange Server 2013 pocket consultant : configuration & clients - Stanek, William R. (Microsoft Press, 2013)
Portable and precise, this pocket-sized guide delivers ready answers for administering configuration and clients in Exchange Server 2013. Zero in on core tasks through quick-reference tables, instructions, and lists. You'll get the focused information you need to save time and get the job done-whether at your desk or in the field. Coverage includes: Deploying Exchange Server 2013 Administration essentials Using Exchange Management Shell Managing Exchange clients User and contact administration Mailbox administration Working with Distribution Groups and Address Lists Implementing security.